2011
DOI: 10.1007/s12185-011-0927-3
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of adherence and persistence with iron chelation therapy

Abstract: Due to advances in medical sciences, many chronic diseases that formerly resulted in early death can now be effectively managed with long-term treatment regimens. Patients with potentially fatal anemias, for example, can be treated with ongoing blood transfusions and iron chelation therapy. Ensuring adherence and persistence is challenging, as the benefits of therapy are not perceived immediately. Poor adherence severely compromises the effectiveness of treatment and, therefore, improving compliance in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 37 publications
2
52
0
3
Order By: Relevance
“…In two studies of deferasirox that evaluated patient-reported outcomes, injection-site reactions were cited as being one of the reasons for preferring deferasirox to deferoxamine [36,37]. Tolerability issues, such as the injection-site reactions associated with deferoxamine and the GI side effects associated with deferasirox, are a concern for older patients with MDS that impact adherence [38]. …”
Section: Adherence To Ictmentioning
confidence: 99%
“…In two studies of deferasirox that evaluated patient-reported outcomes, injection-site reactions were cited as being one of the reasons for preferring deferasirox to deferoxamine [36,37]. Tolerability issues, such as the injection-site reactions associated with deferoxamine and the GI side effects associated with deferasirox, are a concern for older patients with MDS that impact adherence [38]. …”
Section: Adherence To Ictmentioning
confidence: 99%
“…Deferoxamine (DFO) has been the principal iron chelating therapy for many years, and it has altered the prognosis of iron overload in patients with transfusion‐dependent β‐thalassaemia . DFO is effective only when administered parenterally, using infusion pumps that dispense an equal amount of drug over a 10–12 h period for 4–7 times a week.…”
Section: Introductionmentioning
confidence: 99%
“…DFO is effective only when administered parenterally, using infusion pumps that dispense an equal amount of drug over a 10–12 h period for 4–7 times a week. This modality of treatment, although effective, is very painful and locally irritating . Thus, it is not surprising that adherence with such a difficult treatment decreases over time …”
Section: Introductionmentioning
confidence: 99%
“…The economic, clinical, and humanistic impact of iron overload may become substantial, and poor adherence to ICTs has been shown to result in serum ferritin targets to not be achieved, which negatively impacts costs, morbitidy and mortality, and healthrelated quality of life [31,[40][41][42]. The long-term ramifications of nonadherence to ICTs in persons with iron overload may manifest in severe clinical complications, particularly hepatic failure, iron-induced cardiomyopathy, or pancreatic iron deposition [9].…”
Section: Cost Analysismentioning
confidence: 99%
“…It is also important to note that persons with SCD have reported significant barriers in access to health care, particularly those associated with delays in treatment [43]. Predictors of nonadherence in SCD remain complex and multifaceted, and current suggestions state that an integrated team approach involving healthcare providers, family caregivers, and treatment centers be utilized to achieve optimal results with chronic therapies [29,42].…”
Section: Cost Analysismentioning
confidence: 99%